Be creative! : how to think outside the box - Howell , Izzi; Muncaster , Katherine (London Wayland, 2023)
This book helps children learn how to boost their creativity with logic puzzles, challenges and activities. It encourages the reader to think outside the box, take creative risks and find new ways to do things. As well as puzzles, the book explores the stories of creative minds from history to help children learn from the brilliant men and women of the past
Education
Keywords: Creative ability; Critical thinking